2005
DOI: 10.1211/0022357056578
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological comparison of the vasorelaxant action displayed by kaurenoic acid and pimaradienoic acid

Abstract: The vascular effects of two natural occurring diterpenes from the kaurane and pimarane classes were compared. The diterpenes ent-kaur-16-en-19-oic acid (kaurenoic acid; KA) and ent-pimara-8(14), 15-dien-19-oic acid (pimaradienoic acid; PA) were tested for their antispasmodic activity on isolated rat aorta. Vascular reactivity experiments, using standard muscle bath procedures, showed that KA and PA (both at 50 and 100 microM) inhibited phenylephrine and KCl-induced contraction in both endothelium-intact and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…On the other hand, pimaradienoic acid possesses a double bond between C-15 and C-16 that is not present in kaurenoic acid. A pharmacological comparison of the vascular effects of these two natural occurring diterpenes showed that that pimaradienoic acid is more effective than kaurenoic acid at inhibiting phenylephrine, KCl and CaCl 2 -induced aorta contraction (Tirapelli et al, 2005). Moreover, the equilibrium period for pimaradienoic acid to achieve its maximal inhibitory response, which is more pronounced than that found for kaurenoic acid, is shorter than that observed for kaurenoic acid.…”
Section: Structure-activity Relationship Of Kauranes and Pimaranesmentioning
confidence: 91%
“…On the other hand, pimaradienoic acid possesses a double bond between C-15 and C-16 that is not present in kaurenoic acid. A pharmacological comparison of the vascular effects of these two natural occurring diterpenes showed that that pimaradienoic acid is more effective than kaurenoic acid at inhibiting phenylephrine, KCl and CaCl 2 -induced aorta contraction (Tirapelli et al, 2005). Moreover, the equilibrium period for pimaradienoic acid to achieve its maximal inhibitory response, which is more pronounced than that found for kaurenoic acid, is shorter than that observed for kaurenoic acid.…”
Section: Structure-activity Relationship Of Kauranes and Pimaranesmentioning
confidence: 91%
“…Importantly, A. cordata extract protected cartilage degradation and inhibited apoptosis, suggesting the potential to inhibit Correspondence to: Hyun Pyo Kim, College of Pharmacy, Kangwon National University,-9271 E-mail: hpkim@kangwon.ac.kr osteoarthritis (Bae et al, 2006). Among its constituents, pimaradienoic acid and kaurenoic acid have been shown to exert vasorelaxant action (Tirapelli et al, 2005). When the inhibitory activities against COX-1 and COX-2 were measured, several compounds, including pimaradienoic acid and kaurenoic acid, moderately inhibited COX-1, while only kaurenoic acid inhibited COX-2 weakly (Dang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In previous phytochemical investigations, various diterpenes, flavonoids, saponins, and essential oils were isolated from the roots and leaves of this plant (Kang, 1997). Considering the biological studies of these isolated compounds, ent-pimara-8 (14), 15-diene-19-oic acid and ent-kaur-16-en-19-oicacid as major constituents were reported to possess analgesic (Okuyama et al, 1991), anti-tumor (Ryu et al, 1996), anti-inflammatory (Han et al, 1983;1985), vasorelaxant (Ambrosio et al, 2006;Tirapelli et al, 2005), and antimicrobial activities (Porto et al, 2009;Ambrosio et al, 2008). Recent studies on the aerial parts of this plant showed ent- pimara-8(14),15-diene-19-oic acid to be a potent antibacterial constituent (Jeong et al, 2006).…”
Section: Introductionmentioning
confidence: 99%